Jesus" interment in Mark 15:42–47: An identifying factor for Jesus" Jewishness - Hombana, Mphumezi (HTS teologiese studies, 2025)
The story of Jesus’ burial in Mark 15 presents Jewish funeral traditions that show Jesus’ connection to Judaism. This study looks closely at the burial process in Mark, focusing on what happens when Joseph of Arimathea asks for Jesus’ body and makes it ready for burial and where it is placed before the Sabbath starts. It puts these practices into the context of Jewish funeral rituals when Jesus lived. Furthermore, by contextualising these burial customs, this research proposes that Mark uses these rituals to underline Jesus’ conformity to Jewish identity and present a theological continuity between Jesus and the Jewish faith, despite the Gospel’s eventual message to a broader audience. In exploring how these burial practices function as cultural identity markers, this article contributes to scholarship on the Jewishness of Jesus, arguing that Mark’s burial account reinforces a communal and cultural bond that defines Jesus’ identity within his Jewish heritage.Contribution: This article underlines the importance of Jewish funerary customs in Mark 15:42–47 as identity markers affirming Jesus’ Jewishness. By analysing burial practices such as body preparation and timing, it contextualises Jesus’ burial within Second Temple Judaism, demonstrating his alignment with Jewish traditions. This study offers a nuanced perception of how Mark integrates cultural practices to portray theological continuity between Jesus and Judaism while addressing a broader audience.